ASSESSING QUALITY OF LIFE IN HISTORIC CITY - CASE OF SHAHJAHANABAD - Shivani Goel; Rashmi Ashtt; Prasoon Gupta (Journal of Governance and Global Studies, 2025)
historic urban city due to which new infrastructure is needed. But adding new infrastructure is very challenging because of limited space, congested areas, old infrastructure, and poor governance which then leads to slum-like conditions in those areas. These conditions deteriorate the feel of the place and the quality of life of people living there worsens. As the quality of life is not appropriate, people start migrating to other areas for living and these houses are in turn converted to commercial spaces either for storage or small factories. These conversions lead to an increase in footfall of people due to commercialization and the character of the city changed from mixed-use to commercial. There is a need to address the needs of those people to make the area/city livable or provide a better quality of life to residents and workers of that area. To understand this, a case of Shahjahanabad as a model case study for historic cities in India is taken which depicts similar conditions as discussed, have issues related to increases in population, deteriorating infrastructure, residential conversion into commercial, traffic jams, congestion, political and economic adversaries, etc. The paper is an effort to analyze or bring forward the issues faced by the residents/ workers living in historic cities through the parameters of quality of life which has deteriorated over time and suggestions will be provided to upgrade the city life.